2010
DOI: 10.1007/s13277-010-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-mediated ADAM9 gene silencing inhibits metastasis of adenoid cystic carcinoma cells

Abstract: A disintegrin and metalloproteinase 9 (ADAM9) is a type I transmembrane protein that has been associated with cancer development and metastases. Here, we show that ADAM9 is highly expressed in metastatic cancer tissues and in an adenoid cystic carcinoma cell line with a high metastatic potential. Using RNA interference for gene silencing, we show that ADAM9 is essential for in vitro cancer cell proliferation and invasion as well as in vivo cancer metastasis in an experimental murine model of lung metastases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…These observations are in line with a previous study in which downregulation of ADAM9 in cystic carcinoma cells led to less lung metastasis, as determined by i.v. injection into nude mice (36). In agreement, overexpression of ADAM9 in lung cancer cells resulted in both brain and lung metastases, whereas mock-transfected cells only colonized the lungs (37,38).…”
Section: Discussionsupporting
confidence: 57%
“…These observations are in line with a previous study in which downregulation of ADAM9 in cystic carcinoma cells led to less lung metastasis, as determined by i.v. injection into nude mice (36). In agreement, overexpression of ADAM9 in lung cancer cells resulted in both brain and lung metastases, whereas mock-transfected cells only colonized the lungs (37,38).…”
Section: Discussionsupporting
confidence: 57%
“…These consecutive events result in alterations in a large number of genes and signaling pathways (35). ADAM9, a member of the ADAM family, appears to be involved in lung cancer progression and metastasis (19,20). A previous study demonstrated that the downregulation of endogenous ADAM9 by RNAi was capable of inhibiting adenoid cystic carcinoma cell growth and metastasis in vitro and in vivo (20).…”
Section: Discussionmentioning
confidence: 99%
“…ADAM9, a member of the ADAM family, appears to be involved in lung cancer progression and metastasis (19,20). A previous study demonstrated that the downregulation of endogenous ADAM9 by RNAi was capable of inhibiting adenoid cystic carcinoma cell growth and metastasis in vitro and in vivo (20). In addition, previous studies have confirmed that Stat3 is involved in cancer migration and invasion, and blocking the activity of Stat3 has been observed to inhibit cancer cell migration and invasion (6-16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral medications to treat HCC are limited. Sorafenib, a multi-kinase inhibitor effective in enhancing overall survival of patients with advanced HCC [117], is the only oral drug recently approved by the US Food and Drug Administration. Sorafenib has antiproliferative activity in liver cancer cell lines.…”
Section: Mirnas In Treatment Stratification Of Hccmentioning
confidence: 99%